MENGATASI KESULITAN MEMBAGI WAKTU ANTARA BELAJAR DAN ORGANISASI MELALUI KONSELING BEHAVIORISTIK TEKNIK SELF MANAGEMENT - Tesa Elviana; Edris Zamroni; Susilo Rahardjo (Universitas Muria Kudus, 2022)
The aims of this study are: 1) To find out the factors that cause difficulties in dividing time between learning and organization. 2) Overcoming the problem of learning time management of students who are actively organized by using behavioristic counseling with Self Management techniques. This research uses qualitative research in the form of case studies. The subjects studied were AL and MK students at SMK 3 Pati in the academic year 2020/2021. Data collection techniques carried out by researchers are interviews, observation and documentation.Based on the results of the study, it shows that after the counselee has not been able to manage study time properly because of delaying assignments due to organizational friends, not taking full lessons due to missing lessons, and not having a good daily schedule. To assist counselees in overcoming difficulties in managing time, counselors apply Behavioral Self Management counseling techniques that are proven to be able to overcome time management difficulties between studying and organizing by not procrastinating on assignments, participating fully in lessons so as not to miss lessons, and having a daily schedule and having priorities.